Effect of physical and chemical treatments on breaking the seed dormancy of Caesalpinia bonduc (L.) Roxb. - Jaya Rathi, J; Sasirekha, R; Ranjith Kumar, R (Plant Science Today, 2021)
Caesalpinia bonduc (L.) Roxb. is a medicinal plant belonging to the family Caesalpiniaceae was used for the present study. It is a prickly shrub widely distributed all over the world. Keeping the economic and social medicinal uses of C. bonduc seeds are being used widely in Folk, Ayurvedha, Siddha, Unani medicines to treat skin disease, eyesores, cancer, asthma, tuberculorosis, fever, toothaches etc. The aim of this study is to determine the requirements for breaking seed dormancy and germination of C. bonduc. The germination is prevented due to hard seed coat. C. bonduc seeds were experimented with various physical and chemical treatments to break the dormancy. The seeds were subjected to various treatments like mechanical scarification, dry heat method, light, hot water, acid scarification, inorganic compounds, plant growth regulators etc. The seeds treatment with mechanical scarification at 50, 40 and 30 seconds showed 100%, 80% and 10% of germination, whereas no changes was observed in dry heat. White light treatment showed 100% germination at 48 hrs, whereas darkness and red light showed least germination of about 10%. The hot-water treatment showed 100% germination. In chemical treatments, concentrated sulphuric acid scarification showed highest germination percentage, whereas lowest germination was found in nitric acid. Among the plant growth regulators, Gibberellic acid showed 100% germination whereas 2-isopentyl adenine showed least germination of 10% at 50 ppm. Results of this study prove that mechanical scarification was the most effective treatment to overcome dormancy of seeds in C. bonduc.